Elucidation of the interaction between fructose and key aroma compounds in watermelon juice via Raman spectroscopy and nuclear magnetic resonance. (September 2022) - Yang, Fan; Chen, Erbao; Dai, Yixin; Xu, Ying; Liu, Ye; Bi, Shuang
Graphical abstract: Highlights: 1 Key odor compounds were quantified by stable isotope dilution assay. 2 Three aldehydes combined with fructose via hydrogen bonds. 3 Acetophenone interacted with fructose via π-π interaction. 4 Temperature and oxidation effects on aroma release were discussed. Abstract: Food matrix composition is an important factor affecting the release of aroma compounds. In the present study, four key aroma compounds (namely, hexanal, nonanal, ( E )-2-nonenal, and acetophenone) were quantified in watermelon juice by stable isotope dilution assay. Using Raman spectroscopy and 1 H NMR, it was found that hexanal, nonanal, and ( E )-2-nonenal combine with fructose via hydrogen bonds, whereas acetophenone interact with fructose via π-π interaction. Entropy compensation at higher temperatures may explain the decrease in the contents of hexanal, nonanal, and ( E )-2-nonenal released from the system. In contrast, the decrease in the contents of these aroma compounds by H2 O2 might be due to the formation of a greater number of hydrogen bonds with carboxyl groups oxidized by aldehydes. This study contributes to further the understanding on the interaction between aroma compounds and fructose, thus offering practical insights on the regulation and control of flavor development in watermelon juice.